Visible light driven doped CeO2 for the treatment of pharmaceuticals in wastewater: A review. (October 2022) - Iqbal, Jibran; Shah, Noor S.; Khan, Zia Ul Haq; Rizwan, Muhammad; Murtaza, Behzad; Jamil, Farrukh; Shah, Afzal; Ullah, Aman; Nazzal, Yousef; Howari, Fares
Abstract: The high-level contamination of pharmaceuticals in aquatic environment, and their toxicities is a serious issue. This review highlights the use of ceria photocatalyst for treatment of pharmaceuticals. Cerium oxide (CeO2 ) with high oxygen storage, ecofriendly properties, reusability, and photostability contrary to other metal oxides photocatalysts is reportedly a better choice. However, ceria with high band gap energy show photoactivity mainly under UV light. This review highlights pharmaceuticals contamination in water, their contamination level, and toxicities and properties of CeO2 and different approaches used for extending photoactivity of CeO2 under visible irradiation. Metals and non-metals doping is found to promote greatly photoactivity of CeO2 under visible irradiation by narrowing band gap, shift in absorption edge to visible region, crystal defects and yield of oxygen vacancy, lower recombination of conduction band electrons and valence band holes and increasing surface area. The visible irradiation of CeO2 is found to produce hydroxyl radical (OH) and superoxide radical (O2 – ) which contribute in pharmaceuticals degradation. The electron paramagnetic resonance spectroscopy and radical scavenger studies confirmed the formation of reactive oxygen species from CeO2 photoactivation. Doping was found to incorporate into the lattice of CeO2 and improve reusability and stability of CeO2 photocatalyst. The suggested mechanisms involved in the treatment of pharmaceuticals through OH and O2 – is discussed. Furthermore, the outlook and future challenges in the use CeO2 for photocatalytic degradation of pharmaceuticals and other organic pollutants are evaluated. Graphical abstract: Unlabelled Image Highlights: The sources and issues of different pharmaceuticals in water are discussed. The design and importance of CeO2 for degradation under visible light is discussed. Key steps and processes in the modification and activation of CeO2 are discussed. Effects of different factors affecting performance of the photocatalyst is discussed. Steps necessary for future perspective and potential use of CeO2 are discussed.